Lemma, Inc. hydrogen peroxide plant - Cendaña, Emma Q.; Miravalles, Lemuel M. (Diliman, Quezon City College of Engineering, 1967)
Capacity: 5 tons/24 hr-day -- Fixed capital investment: 14,612,540 -- Operating cost at maximum production: 2,705,054 -- Sales at maximum production: 4,940,000 -- Pay-off time: 4 years -- Break-even point: 2.8 tons/ 24 hr-day -- Plant location: Pasig, Rizal
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Chemical plants; Hydrogen peroxide